Advances in research on attachment-related psychotherapy processes: seven teaching points for trainees and supervisors - Alessandro Talia; Svenja Taubner; Madeleine Miller-Bottome (Research in Psychotherapy, 2019)
While the rich body of attachment theory and research has inspired many psychotherapists, trainees and less experienced clinicians interested in attachment-informed work can often feel unsure about what processes are attachment-related and how to attend to them during therapy. Recent advances in attachment-informed psychotherapy research offer some practical guidance. Studies published over the last five years show that patients and therapists of different attachment classifications communicate in distinct ways during therapy sessions. In particular, Talia and his colleagues have introduced the Patient Attachment Coding System and the Therapist Attunement Scales, two measures that accurately predict patients’ and therapists’ Adult Attachment Interview and Reflective Functioning score based on the occurrence of distinct communication markers during therapy sessions. This paper discusses the implications of these recent studies for psychotherapy training and presents seven teaching points for supervisors and for the next generation of clinicians.